Representation of inter-patient relations within electronic healthcare record architectures. - Duftschmid, Georg (Medical informatics and the intrenet in medicine :an international journal of information processing in health care.)
Inter-patient relations are relevant in numerous areas of medicine, such as in the examination of genetic disorders, environmental causes of diseases, and in epidemiology. Therefore, it is essential that inter-patient relations be well integrated into the electronic health care record (EHCR). In the present paper we will show how inter-patient relations can be modelled within the three important EHCR architectures CEN ENV 13606, HL7 Clinical Document Architecture, and GEHR. We will use a general model for the specification of inter-patient relations as our reference model, which covers genetic and non-genetic kinship relations as well as temporary communities of persons